The Influence Of Management Information Systems On Employee Performance With Transformational Leadership Style As A Moderating Variable - Yudi Nur Supriadi; Yeheskial Nggandung; Haruni Ode; Afif Deni Irawan; Nurhayati Nurhayati (UNIVED Press, 2025)
This study is a quantitative study with an explanatory approach, namely an approach that emphasizes the three studies mentioned explicitly above as references and main references. The data used in this article is primary data that researchers distributed to 300 Mitra Bangunan employees spread throughout Indonesia. The data was analyzed using the smart PLS 4.0 analysis tool.